2012
DOI: 10.1007/s00281-012-0346-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of lymphatic filarial disease

Abstract: Although two-thirds of the 120 million people infected with lymph-dwelling filarial parasites have subclinical infections, ~ 40 million have lymphedema and/or other pathologic manifestations including hydroceles (and other forms of urogenital disease), episodic adenolymphangitis, tropical pulmonary eosinophilia, lymphedema, and (in its most severe form) elephantiasis. Adult filarial worms reside in the lymphatics and lymph nodes and induce changes that result in dilatation of lymphatics and thickening of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 132 publications
(165 reference statements)
0
105
0
2
Order By: Relevance
“…In filariasis, progression of lymphedema, and therefore elephantiasis (the gross tissue changes seen in advanced lymphedema giving rise to skin resembling elephant hide), is considered a two-step process -the first initiated by the filarial parasite and host innate immune system and the second propagated by the host's adaptive immune system and secondary infection (30). With an estimated 120 million people infected by lymph-dwelling filarial parasites, 40 million have lymphedema and secondary infections, thereby creating an enormous global disease burden.…”
Section: Immunity Inflammation and Infectionmentioning
confidence: 99%
“…In filariasis, progression of lymphedema, and therefore elephantiasis (the gross tissue changes seen in advanced lymphedema giving rise to skin resembling elephant hide), is considered a two-step process -the first initiated by the filarial parasite and host innate immune system and the second propagated by the host's adaptive immune system and secondary infection (30). With an estimated 120 million people infected by lymph-dwelling filarial parasites, 40 million have lymphedema and secondary infections, thereby creating an enormous global disease burden.…”
Section: Immunity Inflammation and Infectionmentioning
confidence: 99%
“…Recurrent episodes of bacterial infections further damage the tiny lymphatic vessels in the skin, reducing their ability to drain fluid efficiently. Nevertheless LF is associated with the elevated levels of pro-inflammatory and profibrotic cytokines [2]. Notably, the expression of genes involved in cellular adhesion, inflammation and lymphangiogenesis were altered.…”
Section: Introductionmentioning
confidence: 99%
“…Existing data support the involvement of pro-inflammatory cytokines namely Interleukin-6 (IL-6) and Interleukin-8 (IL-8) were significantly elevated in LF [2], which plays a key role in the initiation of irreversible swelling, fibrosis [11,12] and regenerative processes of hepatic structure and function [13,14]. Hence, we investigated the potential abilities of thymol against hepatotoxicity, bacterial infection; oxidative stress, elevated cytokines and inflammatory markers expression in response to paracetamol induced effects in WRL-68 liver cells.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of proinflammatory cytokines, possibly of innate origin, in the pathogenesis of lymphedema, has been further strengthened by a series of studies in humans in either the early or late stages or lymphedema. Studies have shown that individuals with chronic lymphatic pathology have elevated levels of C-reactive protein (an acute phase protein, indicating an acute inflammatory response), pro-inflammatory cytokines such as TNF-α, IL-6 and soluble TNF receptor, endothelin-1, IL-2, as well as IL-8, MIP-1α, MIP-1β, MCP-1, TARC and IP-10 in the peripheral circulation (6). Similarly, while patients with both acute and chronic manifestations of LF have elevated circulating levels of IL-6 and IL-8, only those with chronic disease manifestations have elevated levels of sTNF receptors (63).…”
Section: Pathogenesis Of Filarial Diseasementioning
confidence: 99%